The words of the past period in modern historical novel of Vasil Shklyar "Zalyshenets. Chornyi Voron" (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article investigates the stylistic and semantic features of obsolete vocabulary presented in the modern historical novel of Vasil Shklyar "Zalyshenets. Chornyi Voron". The military (Battle) vocabulary, one of the most numerous of the lexical-semantic subgroups − "names of military ranks and posts" on the one hand, in the Ukrainian insurgent army, on the other hand – in the Red Army is analyzed. It focuses on Sovietisms related to administrative, social and political life of that time.
Keywords: obsolete vocabulary; the names of military ranks and posts; Sovietism; lexical-semantic group